Developing a form-process framework to describe the functioning of semi-arid alluvial fans in the Baviaanskloof Valley, South Africa - Bobbins, Kerry Leigh (Rhodes University, Faculty of Science, Department of Geography, 2012)
The Baviaanskloof catchment is a semi-arid catchment located in the Cape Fold Mountains of South Africa. Little is known about the functioning of the complicated Baviaanskloof fluvial system and the role alluvial fans in the fluvial landscape. This thesis will contribute to field of geomorphology and, more specifically, to the field of fan morphometry by producing a standalone fan framework outlining methods to investigate the influence of external and internal control variables on alluvial fans. In this thesis, outcomes of the applied framework and case study are used to develop fan restoration guidelines for the Baviaanskloof Valley. The framework incorporates external and internal fan control variables at a valley-wide and local fan scale. External control variables include accommodation space, base-level change, and drainage basin inputs. Internal control variables include fan style, morphometry and fan channels. In order to apply the framework, fan morphometry data was required. This data was collected by creating a spatial plan of fans and basins in the valley. Outcomes of the applied framework include; an understanding of baselevel change on fans, relationships between fan basin characteristics and the fan surface and insight into fan channel processes. Results of the applied framework are investigated further using bivariate (correlation matrix) and multivariate (principle component analysis and regression analysis) analysis techniques. Significant relationships identified are: drainage basin area versus fan area, fan area and fan slope and drainage basin ruggedness and basin size. The primary outcomes of this thesis include an alluvial fan form-process framework, key considerations to be included in alluvial fan restoration projects and fan restoration guidelines. Contributions of this thesis to broader alluvial fan morphology science includes new insights into general fan literature by compiling a form-process alluvial fan classification framework to identify external and internal fan control variables and identify fan form. Additions have been made to Clarke's (2010) evolutionary stages to describe stages 4 and 5 of fan evolution that has been adapted to describe fan evolution and differentiate between stages of mature fan evolution. This thesis has also contributed to the study of alluvial fans in South Africa, particularly in the Baviaanskloof Valley. The layout of the procedural guidelines and key considerations for an alluvial fan project provides a guide for rapid fan assessment for maximum cost and time benefits for stakeholders.
Keywords: Alluvial fans -- Research -- South Africa; Sedimentation and deposition -- Research -- South Africa; Geomorphology -- Research -- South Africa